Evaluation of supine pressure test in the prediction of pregnancy-induced hypertension in a low socioeconomic group (Colombia Medica, 1990)
The hypertension induced by pregnancy (HIP) is an important cause of maternal-perinatal morbidity and mortality. The present study evaluated the efficiency of the rollover test (ROT) in predicting the later development of HIP in an obstetrical population resident in a marginal area of the city of Cali, Colombia. The ROT was practiced on 127 patients with a gestational age between 28-32 weeks without previous pathology. Of these 127 patients, 25 had a positive ROT, and of them, 60% had associated HIP; 102 patients had a negative ROT, which was associated with a normal outcome of the pregnancy in 91.2%. We found sensibility, 62.5%; specificity, 90.3%; a predictive value of the positive test, 60%; and a predictive value for a negative test, 91.2%In conclusion, we believe that the ROT should be used routinely in the antenatal clinic for all pregnant women between 28-32 weeks because it is safe, inexpensive, and easy to perform, requiring only a blood pressure cuff and a short period of time for its execution.